Hubungan Shift Kerja dan Usia Terhadap Kelelahan Pada Karyawan Bagian Produksi Di Pt X. Kota Batam Tahun 2023 - Agustiana, Indri; yanti, Novi; Rizal, Chandra (Fakultas Ilmu Kesehatan, Universitas Ibnu Sina, 2023)
This study aims to determine the relationship of work shifts and age to job fatigue in production employees at PT X Batam City in 2023. The type of research used is quantitative. The population of this study were employees of the production unit (BU3) in line 6 as many as 200 respondents. The research instrument used in this study was a questionnaire. The sampling technique used in this study was simple random sampling with 133 respondents and statistical analysis using the chi square test. The results showed that there was a relationship between work shift and fatigue (p value = 0.000 < α = 0.05) and no relationship between age and fatigue (p value = 0.286 > α = 0.05). It is concluded that there is a significant relationship between work shift and job fatigue and no significant relationship between age and job fatigue. It is suggested that PT X Batam City pay more attention to employees such as providing food & beverage facilities, socializing 5 - 10 minutes warm-up activities to employees.